Llama Llama learns to swim - Dewdney, Anna; Dewdney, Anna; Penguin Young Readers Group (New York, New York Penguin Young Readers Licences, an imprint of Penguin Random House LLC, 2018)
Luna Giraffe has the fantastic idea to spend an afternoon playing at the beach. Fantastic except for one little detail ... Llama Llama can't swim! So he does what any frightened little Llama would do: He asks his mama for help. Can Mama Llama's swimming lessons help Llama overcome his fear of the ocean, or will he be stuck on the shore all summer?
"As seen on Netflix"--Cover
Accelerated reader
113610
Keywords: Llama Llama -- Juvenile fiction; Llamas -- Juvenile fiction; Swimming -- Juvenile fiction; Juvenile Fiction -- Animals; Juvenile Fiction -- Media Tie-In; Juvenile Fiction -- Sports & Recreation -- Water Sports; Picture books for children; Picture books; Juvenile works; Fiction